2019
DOI: 10.1021/acs.joc.9b00073
|View full text |Cite
|
Sign up to set email alerts
|

Induced Circular Dichroism of Achiral Cyclic Bisurea via Hydrogen Bonds with Chiral Carboxylates

Abstract: Chiral induction properties of achiral bisurea derivatives by binding tetrabutylammonium salts of N-acetylated chiral carboxylates (Ac-AlaO–, Ac-ValO–, Ac-LeuO–, and Ac-PheO–) was studied. Ultraviolet–visible titrations showed 1:1 complex formation between the bisureas and the carboxylates. The calculated association constants of cyclic bisurea (1a) were 5–10 times larger than those of the acyclic derivative (2), and 1a showed the highest binding affinity for Ac-LeuO–. While circular dichroism (CD) of both 1a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 38 publications
(75 reference statements)
0
10
0
1
Order By: Relevance
“…The hexaurea cage developed by Davis and co‐workers ( 23 , Figure 10c) [60] can not only selectively and effectively bind glucose in water, but also can work as a chirality sensor for this monosaccharide, [61] and could be used for the continuous monitoring of glucose concentration in blood. A bisurea macrocycle ( 24 , Figure 10d) [62] was used for the chiroptical sensing of chiral carboxylates in nonpolar solvents through hydrogen bonding and C−H⋅⋅⋅π interactions. DFT calculations reveal that a twisted conformation is induced after binding to chiral carboxylates.…”
Section: Chiroptical Sensing With Relatively Rigid Hostsmentioning
confidence: 99%
“…The hexaurea cage developed by Davis and co‐workers ( 23 , Figure 10c) [60] can not only selectively and effectively bind glucose in water, but also can work as a chirality sensor for this monosaccharide, [61] and could be used for the continuous monitoring of glucose concentration in blood. A bisurea macrocycle ( 24 , Figure 10d) [62] was used for the chiroptical sensing of chiral carboxylates in nonpolar solvents through hydrogen bonding and C−H⋅⋅⋅π interactions. DFT calculations reveal that a twisted conformation is induced after binding to chiral carboxylates.…”
Section: Chiroptical Sensing With Relatively Rigid Hostsmentioning
confidence: 99%
“…Kondo et al reported [17] the synthesis of a bisurea-based macrocycle 6 and an acyclic bisurea analog for the purpose of chirality sensing of chiral carboxylic acid anions (Figure 4). These bisureas form a 1:1 complex with chiral carboxylates through hydrogen-bonding interaction in MeCN with high binding affinity up to 10 7 M −1 .…”
Section: Macrocyclic Naphthalene Derivativesmentioning
confidence: 99%
“…Different spectroscopic techniques such as NMR, UV-visible absorption, or circular dichroism have traditionally been used to demonstrate supramolecular complexation. We have used three complementary techniques: circular dichroism to determine whether the complex was formed or not, NMR for the stoichiometry elucidation and UV-visible spectrophotometry 18 to obtain the association equilibrium constant and the spectra of the supramolecular complexes.…”
Section: -Inclusion Complexesmentioning
confidence: 99%